Experimental and analytical investigations of prefabricated segmental concrete beams post-tensioned with unbonded steel/FRP tendons subjected to impact loading - Tran, D.T.; Pham, Thong; Hao, Hong (2024)
Studies of prefabricated segmental concrete beams (PSCBs) under impact loading are extremely scarce, especially those constructed with geopolymer concrete (GPC) and non-corrodible fibre-reinforced polymer (FRP) tendons. This study conducts experimental tests to explore the impact performance of PSCBs made of GPC and post-tensioned with FRP/steel tendons. An analytical model for predicting the impact response of PSCBs is also derived. The test results show that different from monolithic beams, the damage in PSCBs is mainly concentrated around segment joints due to joint openings that led to the beam failure by concrete spalling. The PSCBs with carbon-FRP tendons and steel tendons show similar damage patterns. Under a similar condition, the difference in the displacement response of these two beams is less than 4 %. A similar trend in the generated impact load and reaction force is also observed. These two beams reach the first peak and plateau region of impact load and the maximum reaction force at similar times. Overall, the PSCB with carbon-FRP and steel tendons exhibits comparable impact performances. These results manifest the applicability of carbon-FRP tendons in PSCBs against impact loads, as a feasible and durable alternative to conventional steel tendons. Furthermore, theoretical derivations are conducted to derive a simplified analytical model for predicting the impact response of simply supported segmental beams. This analytical model is based on a mass-spring-damper system and a nonlinear sectional analysis, considering the local response at the impact zone, global elastic and inelastic behaviours of segmental beams, imperfections in segment interfaces, nonlinear behaviours of material properties and strain rate effects. The proposed analytical model can facilitate the analysis and design of segmental beams.